Addressing Occupational Fatigue in Nurses: Current State of Fatigue Risk Management in Hospitals, Part 1. (September 2017) - Steege, Linsey M.; Pinekenstein, Barbara J.; Rainbow, Jessica G.; Arsenault Knudsen, Élise
Abstract : OBJECTIVE: The aim of this study was to describe the current state of fatigue risk management systems (FRMS) to address nurse fatigue in hospitals. BACKGROUND: Although multiple studies have examined sources and consequences of fatigue, little is known about the current state of FRMS. METHODS: This study used a sequential exploratory mixed-method design including a survey of nurse leaders from across the United States. FINDINGS: Although healthcare organizations have implemented strategies to address fatigue, most participants' organizations did not have a formal FRMS in place. Monitoring individual nurses' levels of fatigue and using tools to predict fatigue risk were rare. CONCLUSIONS: Significant opportunities exist to implement formal FRMS in healthcare. Nursing leaders, in partnership with other organizational leaders, should develop a formal plan to monitor fatigue and implement multiple levels of interventions to prevent fatigue and mitigate its consequences.